Research of the application of banking institutions' rating factors under the conditions of development of enterprises creditability model using the economic and mathematical methods - Furyk, V. H.; Posesor, A. V.; Teptia, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The possibility of development and application of common rating factors of enterprises' creditability — borrowers with banking institutions has been studied. The evaluation model of enterprises' creditability using the economic and mathematical calculations has been developed.